Meningkatkan Keberfungsian Keluarga melalui Family Rituals dan Relevansinya terhadap Budaya Anti Kekerasan Seksual - Jusmiati; Yulia; Zuhra (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2022)
Sexual violence in Indonesia is a very crucial problem. Data on sexual violence shows a very significant increase from year to year. One of the main causes of this violence is the occurrence of family dysfunction which has an impact on the low culture of anti-violence, both in the context of the family and society at large. This study aims to deeply examine how to improve family function through family rituals and explain its relevance to anti-sexual violence culture. This research is based on library data such as journal articles and books as well as online data. The data were analyzed in terms of content (content analysis) with a psychological approach, which more specifically used the concept of family functioning from McMaster's perspective. This study shows that family rituals consisting of eating together, holidays and important moments can increase family functioning optimally. The family ritual is not just a routine, but becomes a valuable moment for the family to foster harmony, internalization and socialization. In this context, the functioning of the family has a very strong relevance to foster a culture of anti-violence, both through its cognitive, effective and psychomotor roles. This research also states that the best solution to create an anti-sexual violence culture must start from simple things. Among them is determining meaningful family rituals. Importantly, these family rituals enhance the functioning of the family as the first madrasa (al-madrasah al-ula) both in the context of education and in the context of protection from all forms of sexual violence.